2010
DOI: 10.1111/j.1365-313x.2010.04124.x
|View full text |Cite
|
Sign up to set email alerts
|

Research on plant abiotic stress responses in the post‐genome era: past, present and future

Abstract: SUMMARYUnderstanding abiotic stress responses in plants is an important and challenging topic in plant research. Physiological and molecular biological analyses have allowed us to draw a picture of abiotic stress responses in various plants, and determination of the Arabidopsis genome sequence has had a great impact on this research field. The availability of the complete genome sequence has facilitated access to essential information for all genes, e.g. gene products and their function, transcript levels, put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
640
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,044 publications
(653 citation statements)
references
References 123 publications
6
640
0
7
Order By: Relevance
“…It suggested that AOS might involve in ABA signaling pathway by stimulating ABA synthesis to induce expression of drought resistance genes and to improve capacity of drought resistance. In higher plants, P5CS gene, which is one of the key genes for proline synthesis from glutamate and ornithine, could be induced and up-regulated by drought stress [35,36]. Our results showed that P5CS in wheat leaves was induced and up-regulated by exogenous AOS under drought condition.…”
Section: Discussionmentioning
confidence: 61%
“…It suggested that AOS might involve in ABA signaling pathway by stimulating ABA synthesis to induce expression of drought resistance genes and to improve capacity of drought resistance. In higher plants, P5CS gene, which is one of the key genes for proline synthesis from glutamate and ornithine, could be induced and up-regulated by drought stress [35,36]. Our results showed that P5CS in wheat leaves was induced and up-regulated by exogenous AOS under drought condition.…”
Section: Discussionmentioning
confidence: 61%
“…Although only a fraction of the metabolic phenotype can be measured, due to the high connectivity in metabolic networks 34 , the profiles carry information about other unmeasured traits 41 . Regression-based analyses have shown that metabolite and enzyme activity profiles provide an integrative metabolic phenotype that is predictive of biomass 33,34,42,43 , heterosis 44 , and, to a lesser extent, abiotic stress tolerance in plants 45 .…”
Section: Resultsmentioning
confidence: 99%
“…SUCROSE NONFERMENTING1-RELATED PROTEIN KINASES2 (SnRK2s) are a family of plant-specific protein kinases implicated in stress and abscisic acid (ABA) signaling (Yoshida et al, 2002;Boudsocq et al, 2004;Kobayashi et al, 2005;Umezawa et al, 2004;Fujii et al, 2007;Shukla and Mattoo, 2008;Fujita et al, 2009;Hirayama et al, 2010;Kulik et al, Figure 1. Phylogenetic analysis of SnRK2.6 proteins.…”
mentioning
confidence: 99%